A comparison of incidence of colorectal cancer and polyps in bowel cancer screening programme patients with symptomatic patients referred under 2 week wait in a demographically matched population. (13th March 2011) - Harrow, P; Nayagam, S; Stafford, N; Hopkins, K; Loke, R
Abstract : Introduction: Traditionally the majority of colorectal cancer has been diagnosed following investigations triggered by symptoms suggestive of malignancy. The National Bowel Cancer Screening Programme has created an alternative route to diagnosis of asymptomatic individuals. Methods: This prospective study compared the incidence of colorectal cancer and adenomatous polyps at colonoscopy and virtual colonoscopy in a population demographically matched for age (60–70) and geographical area (limited to 33 local GP practices). Subjects were either asymptomatic under the Bowel Cancer Screening Programme (BCSP) or symptomatic patients referred under the 2 week wait target (2ww). All endoscopy took place at the Kent & Sussex Hospital between August 2009 and August 2010. Data from colonoscopy reports and histology were analysed. Results: 155 BCSP (mean age 66.0, 61% male) and 127 2ww patients (mean age 64.6, 40% male) fulfilled the entry criteria. Sub-group analysis of both gender groups also found a significant difference in the incidence of adenomatous polyps and no significant difference in the incidence of malignancy. Conclusion: This study demonstrates comparable incidence of colorectal cancers in the two groups. The incidence of polyps was significantly higher in the BCSP group and importantly the polyps found in BCSP were of higher risk of progression to cancer according to the classical adenoma-carcinoma sequence.1 This study demonstrates the efficacy of the BCSP at detecting significant colorectal pathology. The detection of colorectal cancer and high risk polyps are thought to reduce mortality from colorectal cancer.2 The similar detection rates between the symptomatic and asymptomatic groups highlights the poor positive predictive value of symptoms and the assessment currently used for emergency referrals for the diagnosis of colorectal cancer.